Performance limitations of an optical heterodyne CPFSK transmission system due to self-phase modulation - Sarker, B (2002)
A detailed theoretical analysis is presented to evaluate the combined influence of self-phase modulation (SPM) and group velocity dispersion (GVD) of optical fiber on the bit error rate (BER) performance of a heterodyne optical CPFSK system. The power penalty suffered by the system due to the combined influence of GVD and SPM is evaluated from the BER performance results, It is found that the penalty due to SPM at a BER of 10(-9) is significant when the input power exceeds 7 dBm. Further, the CPFSK system with modulation index of 0.5 is less sensitive to the effects of GVD and SPM compared to the system with a modulation index of 1. The theoretical results are in conformity with the experimental results reported earlier. (C) 2002 Elsevier Science Ltd. All rights reserved.